2020
DOI: 10.1007/s10120-020-01100-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of endoscopic ultrasonography in diagnosing invasion depth of early gastric cancer prior to endoscopic submucosal dissection

Abstract: Background and aim Endoscopic ultrasonography is a reliable diagnostic modality for determining indications of endoscopic submucosal dissection for early gastric cancer. We aimed to clarify the clinical significance of endoscopic ultrasonography in the invasion depth diagnosis of early gastric cancer. Methods We retrospectively assessed 1598 consecutive patients with 2001 early gastric cancers who underwent EUS before ESD or surgery between October 2010 and April 2019 at our institution. Lesions were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…There have been a number of AI studies focusing on GC [ 19 , 20 , [32] , [33] , [34] , [35] ]. Most of these previous studies relied on endoscopy, and a small amount of selected medical radiologic technology, such as computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of AI studies focusing on GC [ 19 , 20 , [32] , [33] , [34] , [35] ]. Most of these previous studies relied on endoscopy, and a small amount of selected medical radiologic technology, such as computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnoses are not always accurate. There are several reports about discrepancies between clinical and pathological diagnoses of factors such as size [8][9][10], depth of invasion [11][12][13][14], and histological type [15][16][17]. As with these factors, discrepancies between cUL and pUL sometimes occur in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 A recent study found superior results. 71 The accuracy, sensitivity, specificity, and positive predictive value for invasion depth were 95%, 98%, 69%, and 97%, respectively. However, EUS is not available in all hospitals and may require additional time and enforce a financial burden.…”
Section: How To Decrease Adverse Events?mentioning
confidence: 92%
“…Various authors have been evaluating the accuracy of EUS to predict submucosal invasion, but its accuracy on tumor staging in EGCs was only 70%–76%, with rates of overestimation of the invasion depth as high as 18%–42% 69,70 . A recent study found superior results 71 . The accuracy, sensitivity, specificity, and positive predictive value for invasion depth were 95%, 98%, 69%, and 97%, respectively.…”
Section: How To Improve Patient Selection?mentioning
confidence: 99%